Prospective randomized phase-II trial of ipilimumab/nivolumab versus standard of care in non-clear cell renal cell cancer - results of the SUNNIFORECAST trial - Bergmann, L; Albiges, L; Ahrens, M; Gross-Goupil, M; Boleti, E; Gravis, G; Fléchon, A; Grimm, M-O; Bedke, J; Barthélémy, P; Castellano, D; Mellado, B; et al. (Annals of oncology, 2025)
BACKGROUND: Non-clear cell renal cell cancers (nccRCCs) are a heterogeneous group of more than 20 different entities, but are rarely included in large, randomized trials. Tyrosine kinase inhibitors with or without immune checkpoint inhibition are considered as a standard of care (SOC), but optimal treatment is not yet defined. We designed the first prospective randomized trial comparing ipilimumab/nivolumab to SOC. PATIENTS AND METHODS: We randomized adult patients with previously untreated advanced or metastatic nccRCC 1:1 to nivolumab 3 mg/kg plus ipilimumab 1 mg/kg every 3 weeks for 4 doses followed by fixed dose nivolumab of 240 mg every 2 weeks or 480 mg every 4 weeks or to SOC. Patients were stratified by histology and by IMDC risk score. Central pathology review was mandatory. The primary endpoint was the overall survival (OS) rate at 12 months, secondary endpoints included median OS, response rate, progression-free survival (PFS), safety and quality of life. RESULTS: In total, 157 patients were assigned to receive ipilimumab/nivolumab, and 152 to SOC. The 12-month survival rate was 78% with ipilimumab/nivolumab [95% confidence interval (CI) 71-84%] compared to 68% with SOC (95% CI 60-75%, P = 0.026). Median OS was 33.2 months versus 25.2 months, P = 0.163 [HR 0.81 (0.61-1.099)]. PFS was similar in both arms [HR 0.99 (0.77-1.28)]. The ORR was 32.8% versus 19.3%. No major differences between papillary and non-papillary RCC subtypes were observed for any endpoint. Exploratory analysis showed a significant OS advantage [HR 0.56 (95% CI 0.37-0.86)] associated with a PD-L1 CPS score ≥1. Treatment discontinuation due to toxicity occurred in 27 patients (17%) with ipilimumab/nivolumab and 13 patients (9%) with SOC. CONCLUSIONS: Ipilimumab/nivolumab demonstrated a significantly longer OS at the 12-month milestone and an acceptable toxicity profile. Our results therefore underline a relevant clinical benefit of ipilimumab/nivolumab in previously untreated nccRCC entities compared to current SOC.
Keywords: dospělí; nádory ledvin; Prospective Studies; senioři nad 80 let; Nivolumab; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Carcinoma, Renal Cell; lidé středního věku; Kidney Neoplasms; prospektivní studie; Middle Aged; Aged, 80 and over; karcinom z renálních buněk; non-clear cell renal cell carcinoma; nccRCC; nivolumab; mužské pohlaví; Standard of Care; checkpoint inhibitors; Progression-Free Survival; Ipilimumab; Adult; tyrosine kinase inhibitors; ženské pohlaví; doba přežití bez progrese choroby; standardní péče; lidé; ipilimumab; Aged; Quality of Life; senioři; Male; kvalita života; Female